GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 810 species occurrences available in GBIF matching the query: TaxonKey: Choloepus hoffmanni Peters, 1858. The dataset includes 810 records from 61 constituent datasets: 2 records from ISM Mammalogy Collection. 1 records from UConn Mammals. 9 records from MVZ Mammal Collection (Arctos). 1 records from Fauna y flora de la cuenca media del río Lebrija en Rionegro, Santander. 21 records from KUBI Mammalogy Collection. 17 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 6 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 4 records from CUMV Mammal Collection (Arctos). 63 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 1 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Cowan Tetrapod Collection - Mammals. 1 records from Museu Paraense Emilio Goeldi - Mastozoology Collection. 1 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 50 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from Mastofauna presente en el Alto del Buey, Bahía Solano, Chocó. 4 records from Naturalis Biodiversity Center (NL) - Mammalia. 34 records from Museum of Comparative Zoology, Harvard University. 8 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 2 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 80 records from iNaturalist Research-grade Observations. 1 records from Mammals housed at MHNG, Geneva. 12 records from DMNS Mammal Collection (Arctos). 1 records from Mammal collection, Natural History Museum, University of Oslo. 2 records from Naturalis Biodiversity Center (NL) - Museum collection digitized at storage unit level. 13 records from naturgucker. 4 records from CAS Mammalogy (MAM). 16 records from UMMZ Mammal Collection. 2 records from ICN - Universidad Nacional de Colombia. 18 records from LACM Vertebrate Collection. 1 records from The Mammalia Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 9 records from Natural History Museum (London) Collection Specimens. 2 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 25 records from RBINS DaRWIN. 142 records from NMNH Extant Specimen Records. 8 records from UWBM Mammalogy Collection. 8 records from NYSM Mammals. 2 records from LSUMZ Mammals Collection. 2 records from Paleobiology Database. 1 records from Mammals Specimens. 1 records from (UTC) University of Tennessee Mammals Collection. 6 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 2 records from TTU Mammals Collection. 1 records from UCM Mammal Collection (Arctos). 9 records from PSM Vertebrates Collection. 2 records from Collection Mammalia SMF. 173 records from AMNH Mammal Collections. 1 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 1 records from Inventario de Aves y Mamíferos en humedales del departamento de Córdoba. 1 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 1 records from UAFMC Mammals. 5 records from MSB Mammal Collection (Arctos). 1 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 1 records from Animal Sound Archive. 2 records from Mammalogy Collection - Royal Ontario Museum. 1 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 1 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2007. 17 records from Colección nacional de zoología. 2 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 2 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 1 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 3 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences